Macrophage and Tumor Cell Cross-Talk Is Fundamental for Lung Tumor Progression: We Need to Talk - Sarode, Poonam; Schaefer, Martina Barbara; Grimminger, Friedrich; Seeger, Werner; Savai, Rajkumar (Frontiers in Oncology, 2020)
Regardless of the promising results of certain immune checkpoint blockers, current immunotherapeutics have met a bottleneck concerning response rate, toxicity, and resistance in lung cancer patients. Accumulating evidence forecasts that crosstalk between tumor and immune cells takes a center stage in cancer development by modulating tumor malignancy, immune cell infiltration, and immune evasion in the tumor microenvironment (TME). Cytokines and chemokines secreted by this crosstalk play a major role in cancer development, progression, and therapeutic management. Tumor-associated macrophages (TAMs) represent the major infiltrating population in most human cancers, including lung cancer. In this review we focus on the role of cytokines and chemokines in TAM-tumor cell crosstalk in the lung TME. Given the role of cytokines and chemokines in immunomodulation, we propose that TAM-derived cytokines and chemokines govern the cancer-promoting immune responses in the TME and propose a new immunotherapeutic option for lung cancer treatment.